Male infertility - an overview - Natarajan, Pandiyan (Henry Stewart Talks, 2023)
Causes of infertility in men and women, Diagnosing male infertility, Semen analysis: uses and limitations, Spermatological diagnosis, Medical and surgical management, Sperm retrieval techniques, Algorithm for management, Prevention of male infertility, Fertility preservation